ANALYSIS OF AVIATION SECURITY PERSONNEL IN ASSESSING PASSENGER UNDERSTANDING OF PROHIBITED ITEMS AT ADI SOEMARMO AIRPORT - Qatrunnada, Falah Hanun Qatrunnada; Budiarto, Anton; Rinaldi, Ridho (Proceeding of International Conference of Advanced Transportation, Engineering, and Applied Social Science, 2025)
Aviation security at airports is crucial to ensure air travel’s safety and smooth operation. One of the key factors in maintaining security is passengers’ understanding of prohibited items not allowed onboard. This study analyses the perceptions of Aviation Security (AVSEC) personnel at Adi Soemarmo Airport regarding passengers’ understanding of prohibited items. The research method used is descriptive qualitative with structured interviews and observations at the Passenger Security Check Point (PSCP). The findings show that passengers’ understanding is still low, with many unaware that items such as lighters, scissors, and liquids exceeding the prescribed limit are prohibited. This leads to delays in the screening process and long queues. As an innovation, digital pamphlets and QR codes have been introduced to enhance passenger awareness.